From Tsonga to Moçambicanidade: civil religious dynamics in Mozambican nationalism - Ngale, Samuel Joina (Department of Religious Studies, 2015)
The relationship between the Romande Mission and the Liberation Front of Mozambique (FRELIMO) has been the subject of study by a number of Mozambicanists. Most of them agree that the Romande Mission played a key role in educating nationalist elites and in shaping political consciousness among the Africans. Notwithstanding the relevance of this approach, the current study argues that the Tsonga tribal and Mozambican national identities are civil religious constructs. They resulted from sacrificial ritual performances, the expropriation of traditions and symbols, and the creation of sacred spaces. Formed as a linguistic, cultural, religious and tribal unity, the Tsonga provided a historical genealogy and structural template for the emergence of Moçambicanidade as a civil religion. Drawing upon postcolonial theory and discourse analysis, the thesis uses the analytical category “civil religion” as a focusing lens in order to explore the dynamics of national solidarity in four main archival sources: First, the construction of the Tsonga narratives of the tiMhamba, the Sacred Woods and the expropriation of local traditions recorded in Henri-Alexandre Junod’s, The Life of a South African Tribe; second, the pedigree of a heightened value for union, Protestant work-ethics and education, bequeathed to Eduardo Mondlane and evident in his The Struggle for Mozambique; third, Jose Craveirinha’s deployment of religious and theological symbolism portraying the earliest signs of Moçambicanidade in Xigubo, Cela 1 and Karingana Wa Karingana; and, finally, the successful nation-building story signified by the Constitutional documents. Since the focus of the thesis is on productions of civil religion rather than their reception, evidence is drawn from textual analysis rather than from fieldwork methods. As a consequence of the analysis, the study argues that both Tsonga and Moçambicanidade are subaltern identities to modernity, perhaps destined to fail, but existing within the frame of modernity as its alter ego. By highlighting civil religious constructions of Tsonga and Moçambicanidade, the thesis hopes to shed new light and advance a discussion at the nexus of African religion and politics.